Technological Prospection of Circular Economy’s Methods and Techniques Applied to the Sustainable Economic Development - Sales, Gabriel Fernandes (2021)
As a result of the various environmental problems around the world, we face the need to develop a harmony between the production/consumption of material goods and the environment. In this context, Circular Economy emerges as an innovative concept aiming to develop strategies to mitigate the effects generated by the old linear economy, starting from the creation of a more sustainable ecosystem. The main objective of this research was to carry out a prospective survey on the technological bases of patents: EPO, USPTO and INPI, based on keywords associated with Circular Economy methods and techniques and their applicability. As a result, were found 1.277 patents in different research areas from some countries, subsequently, there has been a significant growth in the granting of new patents over the past few years, motivated by the importance of creating new technologies that aim to solve environmental problems that occur in even more specific areas.